Training of Trainers (ToT) Workshop on Crop-Livestock-Aquaculture Integration Course Module - Ekepu, David; Majaliwa, Jackson Gilbert Mwanjalolo; Nakayiwa, Florence Mayega (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
As part of the AICCRA, the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) are tasked to develop curricula and training materials to accelerate the mainstreaming of Climate Information Services (CIS) and Climate- Smart Agriculture (CSA) into University’s curricula in Africa. This report describes the activities of a training of trainers’ (ToT) workshop on crop-livestock-aquaculture integration course module, held on 24-26 May 2023. The overall objective of the training of trainers’ workshop was to increase awareness and scale adoption/integration of the module on crop-livestock-aquaculture integration across the RUFORUM Network and other non-AICCRA countries. 190 (Male=134; Female=56) participants from 69 universities in 24 countries attended the training. The training increased awareness of crop-livestock-aquaculture integration among academic staff in RUFORUM member universities. Participants indicated strong interest in incorporating the training material into their university curricula and cited several approaches including workshops, seminars, short courses and field demonstrations of the practical aspects of the module.